2020
DOI: 10.21203/rs.3.rs-32531/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Aspartate Aminotransferase to Alanine Aminotransferase Ratio on Admission as Risk Factor for Poor Prognosis in COVID-19 Patients

Abstract: This study aimed to analyze aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio in COVID-19 patients. After exclusion, 567 inpatients were included in this study and separated into two groups according to their AST/ALT ratio on admission. Poor prognosis included death and transfer to other hospitals due to deterioration. Of 567 patients, 56 (9.9%) had AST/ALT ≥ 2. Of the 56 patients, older age (median age 65.5 years), fatigue (29 [51.8%] cases), comorbidities (33 [58.9%] cases) and outcome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(40 reference statements)
2
3
0
1
Order By: Relevance
“…According to the study by Zinellu et al (39), the median De Ritis ratio was 1.33, similar to that reported by Yazar et al in their cohort (38). Furthermore, according to the study by Qin et al (41), the cut-off value of the De Ritis ratio was found to be 1.38; patients with a De Ritis ratio >1.38 upon admission have a significantly poor survival (41). With the hepatic proportion of the AST:ALT ratio of 2.5:1, the hepatocyte turnover may result in a much higher amount of AST in serum compared to ALT.…”
Section: Discussionsupporting
confidence: 75%
“…According to the study by Zinellu et al (39), the median De Ritis ratio was 1.33, similar to that reported by Yazar et al in their cohort (38). Furthermore, according to the study by Qin et al (41), the cut-off value of the De Ritis ratio was found to be 1.38; patients with a De Ritis ratio >1.38 upon admission have a significantly poor survival (41). With the hepatic proportion of the AST:ALT ratio of 2.5:1, the hepatocyte turnover may result in a much higher amount of AST in serum compared to ALT.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, our research demonstrated that AST to ALT ratio has better predictive accuracy for in-hospital mortality than AST or ALT separately, and patients with AST to ALT ratio >1.49 had 54% higher odds for lethal outcome. Consistent results were reported in other studies [60][61][62].…”
Section: Plos Onesupporting
confidence: 93%
“…The analysis of recently published studies reveals the role of systemic vasculitis and cytokine-mediated coagulation disorders, predominantly responsible for multi-organ failure in patients with severe COVID-19 complications. The hematological (lymphocyte count 11,12 , neutrophil count 13 , neutrophil-lymphocyte ratio (NLR)) 14,15 , inflammatory (C-reactive protein (CRP)) 16 , immunological (interleukin (IL)-6) 17 and biochemical (D-dimer 18 , troponin, creatine kinase (CK) 19 biomarkers, as well as procalcitonin (PCT) 16,20 , erythrocyte sedimentation rate (ESR) 21 , aspartate aminotransferase (AST)) 22 , and those particularly related to coagulation cascades in disseminated intravascular coagulation (DIC) 23 and acute respiratory distress syndrome (ARDS) 24 have been reported to be important biomarkers associated with COVID-19 disease. New laboratory biomarkers could be identified through the accurate analysis of multicentric case series; in particular, homocysteine and angiotensin II could play a significant role in this regard 24 .…”
mentioning
confidence: 99%